2019
DOI: 10.3390/nu11112608
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Prognostic Nutritional Index and Dietary Intake in Community-Dwelling Older Adults with Heart Failure: Findings from NHANES III

Abstract: The objective of this study was to examine the association between nutritional status and dietary intake in community-dwelling older adults with heart failure (HF). A cross-sectional analysis of NHANES III data was conducted. The analytic sample was comprised of n = 445 individuals aged 50+ years with congestive HF (54.4% male, 22.9% non-Hispanic Black, 43.8% low-income). Nutritional status was measured using the Prognostic Nutritional Index (PNI). Participants were classified by PNI quintiles with lower PNI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…In the absence of comprehensive nutritional guidance for HF patients, it appears that small increases in energy, protein (red meat), and vegetable consumption are associated with improved nutritional status, which may prevent adverse events in this population. Such positive changes have been shown in a secondary data analysis of survey data from the National Health and Nutrition Examination Survey (NHANES) III using a cross-sectional design [29]. Attempts are being made to systematize the management of a patient with HF after being discharged from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of comprehensive nutritional guidance for HF patients, it appears that small increases in energy, protein (red meat), and vegetable consumption are associated with improved nutritional status, which may prevent adverse events in this population. Such positive changes have been shown in a secondary data analysis of survey data from the National Health and Nutrition Examination Survey (NHANES) III using a cross-sectional design [29]. Attempts are being made to systematize the management of a patient with HF after being discharged from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Except one of the articles published from South Korea [ 29 ], the rest were from the United State ( n = 17) [ 17 – 28 , 30 34 ]. As in study population, except one article paired patients with HF (mostly male) and primary care providers (mostly female), there were 114 patients recruited as research subjects [ 20 ], while the remaining research subjects were received as outpatients ( n = 14) [ 17 19 , 21 27 , 29 , 31 33 ], male ( n = 17) mostly [ 17 19 , 21 34 ], number of recruitment cases between 24 and 445 [ 17 19 , 21 34 ], with an average age of 54–71 years [ 17 19 , 21 34 ]. In terms of patients’ HF characteristics, the mean Left Ventricular Ejection Fraction (LVEF) was between 27 and 68% [ 17 , 20 30 , 32 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is probably the first report exploring the relationships between elemental concentrations in serum for Polish patients with HF and anthropometric measurements as well as biochemical parameters. According to the literature data, the observed deficiencies in micronutrients and elements are common in outpatients with congestive heart failure ( Sattler et al, 2019 ). They have also been conclusively linked to adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it was demonstrated that alterations in the concentrations of both macro-and microminerals may impact on heart failure ( Sattler et al, 2019 ; Weber, Weglicki & Simpson, 2009 ). Disturbed mineral homeostasis in serum, related to the development and progression of HF, may contribute to adverse structural remodelling of the heart and affect its function.…”
Section: Discussionmentioning
confidence: 99%